2011
DOI: 10.1111/j.1447-0756.2011.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 17α‐hydroxyprogesterone caproate in prevention of preterm delivery

Abstract: Weekly administration of 17α-hydroxyprogesterone caproate to pregnant women with a history of preterm delivery was associated with a decrease in preterm delivery and improvement in birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 27 publications
1
31
1
1
Order By: Relevance
“…Thus, a considerable reduction in the complications such as low birth weight, NICU admissions, and neonatal infection is achievable, as it is shown that the length of gestation has a significant impact on the neonatal complications and mortality (28). Some studies support the findings of our study (29-32). For instance, it is shown that 17-alpha-hydroxyl-progestrone-caproate when prescribed as weekly injections for those at risk of preterm labor can prolong pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, a considerable reduction in the complications such as low birth weight, NICU admissions, and neonatal infection is achievable, as it is shown that the length of gestation has a significant impact on the neonatal complications and mortality (28). Some studies support the findings of our study (29-32). For instance, it is shown that 17-alpha-hydroxyl-progestrone-caproate when prescribed as weekly injections for those at risk of preterm labor can prolong pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…A control group of usual care or placebo was compared with progesterone (either type) in 17 studies, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] with cerclage in 12 studies [44][45][46][47][48][49][50][51][52][53][54][55] and with pessary in three studies. [56][57][58] In addition, one study compared 17-OHPC with cerclage 59 and three studies compared natural progesterone with 17-OHPC [60][61][62] (Table 1, and see Supporting information, Figure S2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Since then there have been several randomized clinical trials using various forms of progesterone delivery: vaginal gel, 15 oral micronized gelatin capsules, 16 vaginal micronized capsules, 17 vaginal suppositories, 18 and intramuscular agents, 19 all of which showed some benefit to this therapy. Several systematic review articles and metaanalyses similarly concluded a reduced risk of recurrent preterm delivery with the use of progestogens.…”
Section: Progesteronementioning
confidence: 99%